Development of Gas Kinetic Theory Learning Devices with 2013 Curriculum-based Orientation for Senior High School - Zulhelmi Zulhelmi; Muhammad Nor; Fakhruddin Fakhruddin (Universitas Riau, 2019)
The purpose of this study was to determine the validity and practicality of gas kinetic theory learning devices oriented to 2013 physics curriculum. The place and time of the research was at the Laboratory of Physics Education FKIP University of Riau from June to November 2017. The object of this study was the developed learning devices based on the inquiry approach which includes experimental devices, Learning Plans and Worksheets. This type of research was four D models. Validation was carried out by 3 lecturers of Physics Education Study Program FKIP University of Riau and 2 SMA teachers from Pekanbaru. Limited trial was used to see the practical implementation in class XI IPA 3 of SMAN 4 Pekanbaru. The results of the data analysis obtained that the validity of the gas kinetic theory experimental instrument has very valid category with a logical validation value of 3,47. The validity of the Learning Plan is 3.73 in the very valid category, the validity of the Worksheet is 3.5 whit the very valid category. The practicality of the developed device is 94.1% with a very practical category. The conclusions of the results show that the gas kinetic theory learning devices of High School Oriented Curriculum 2013 were developed valid and high in practicality so that they could be used in physics learning in class XI SMA.